Immunosignals of Oligodendrocyte Markers and Myelin-Associated Proteins Are Critically Affected after Experimental Stroke in Wild-Type and Alzheimer Modeling Mice of Different Ages - Michalski, Dominik; Keck, Anna L.; Grosche, Jens; Martens, Henrik; Härtig, Wolfgang (Frontiers in Cellular Neuroscience, 2018)
Because stroke therapies are still limited and patients are often concerned by long-term sequelae with significant impairment of daily living, elaborated neuroprotective strategies are needed. During the last decades, research substantially improved the knowledge on cellular pathologies responsible for stroke-related tissue damage. In this context, the neurovascular unit (NVU) concept has been established, summarizing the affections of neurons, associated astrocytes and the vasculature. Although oligodendrocytes were already identified to play a major role in other brain pathologies, their role during stroke evolution and long-lasting tissue damage is poorly understood. This study aims to explore oligodendrocyte structures, i.e. oligodendrocytes and their myelin-associated proteins, after experimental focal cerebral ischemia. For translational issues, different ages and genotypes including an Alzheimer-like background were considered to mimic potential co-morbidities. Three- and 12-month-old wildtype and triple-transgenic mice were subjected to unilateral middle cerebral artery occlusion. Immunofluorescence labeling was performed on forebrain tissues affected by 24 hours of ischemia to visualize the oligodendrocyte-specific protein (OSP), the myelin basic protein (MBP) and the neuron-glia antigen 2 (NG2) with reference to the ischemic lesion. Subsequent analyses concomitantly detected the vasculature and the 2’,3’-cyclic nucleotide-3’-phosphodiesterase (CNPase) to consider the NVU concept and to explore the functional relevance of histochemical data on applied oligodendrocyte markers. While the immunosignal of NG2 was found to be nearly absent 24 hours after ischemia onset, enhanced immunoreactivities for OSP and especially MBP were found in close regional association to the vasculature. Added quantitative analyses based on inter-hemispheric differences of MBP-immunoreactivity revealed a shell-like pattern with a significant increase directly in the ischemic core, followed by a gradual decline towards the striatum, the ischemic border zone and the lateral neocortex. This observation was consistent in subsequent analyses on the potential impact of age and genetic background. Furthermore, immunoreactivities for CNPase, MBP and OSP were found to be simultaneously enhanced. In conclusion, this study provides evidence for a critical role of oligodendrocyte structures in the early phase after experimental stroke, strengthening their involvement in the ischemia-affected NVU. Consequently, oligodendrocytes and their myelin-associated proteins may qualify as potential targets for neuroprotective and regenerative approaches in stroke.